Motion characteristics of women`s college soccer matches: Female Athletes in Motion (FAiM) study - Vescovi, J. D.; Favero, T. G. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To quantify the locomotor demands of college female soccer matches and compare the relative proportion of distances in specified velocity bands between players completing an entire half with substitutes. Methods: College female soccer players (n = 113) were assessed during a regular-season match using global positioning system technology. An ANCOVA was used to compare the locomotor characteristics for positions and substitutes, adjusting for duration played. Paired t tests compared the proportion of distances for players substituted out and back into the second half. Results: Defenders covered less total absolute distance than midfielders (first half) and midfielders and forwards (second half) with concomitantly lower work rates. Moderate- and high-intensity running were similar between positions within each half. Midfielders substituted into the match had a lower proportion of moderate-intensity running than those substituted out (15% ± 1.8% vs 19% ± 0.9%), and defenders completing an entire first half had a lower proportion of high-intensity running than defenders substituted in or out (6% ± 1.0% vs 11% ± 1.0% and 16% ± 2.8%). There were no differences in the proportion of distances covered within each velocity band for any position in the second half or for the players substituted out and then back in during the second half. Conclusions: The current findings provide novel insight linking the developmental progression between youth and high-level matches for overall demands and work rates. Moderate- and high-intensity distances cumulatively range from 2100 to 2600 m (26-28% total distance) in female college matches. The high amount of consistency observed for the proportions of distance covered suggest that substitution patterns have little impact on locomotor distribution.